2001
DOI: 10.1292/jvms.63.157
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial of a Feline Pheromone Analogue for Feline Urine Marking.

Abstract: ABSTRACT. Thirty-six cases of feline urine marking problem were collected through the cooperation of veterinary practitioners in the Kanto, Chubu, and Kansai areas in Japan, for an assessment of the clinical effect of treatment with a synthetic analogue of a feline cheek gland pheromone-like product. The mean frequency of urine marking was 14.2 times/week (median, 10; range, 1-77) at pre-treatment week (preW), and decreased significantly from the first week of treatment, dropping to 4.2 times/week (median, 2; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…The home environment of the feline participants varied both within and between studies. All cats were studied in their home environment, this was usually the household although, Ogata and Takeuchi [5] reported that two cats from their study population spent a proportion of time in a cage. In all reports the cats were managed either as indoor only cats or indoor cats with some degree of outdoor access.…”
Section: Types Of Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The home environment of the feline participants varied both within and between studies. All cats were studied in their home environment, this was usually the household although, Ogata and Takeuchi [5] reported that two cats from their study population spent a proportion of time in a cage. In all reports the cats were managed either as indoor only cats or indoor cats with some degree of outdoor access.…”
Section: Types Of Participantsmentioning
confidence: 99%
“…The tendency to offer behavioural advice differed between studies. Frank et al [2]; Landsberg and Wilson [33]; Mills and Mills [6]; Ogata and Takeuchi [5] stated that no specific behavioural advice was offered whereas, Hart et al [21]; King et al [19]; Pryor et al [18] advised owners to employ basic environmental management such as ensuring urine marks were cleaned with an appropriate enzyme based cleaner and keeping litter boxes clean.…”
Section: Types Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medications such as amitriptyline and buspirone have variable success rates and may have undesirable side effects such as sedation or hepatotoxicity (Lindell, Erb, & Houpt, 1997;Overall, 1992). Feliway TM , a derivative of Feline Facial Pheromone (Ceva Animal Health, Lenexa, KS), has been shown to reduce urine marking, aggression, and fear in domestic cats when administered in spray and diffuser forms (Gunn-Moore & Cameron, 2004;Mills & Mills, 2001;Ogata & Takeuchi, 2001). However, these studies have had variable success rates and sprays require daily reapplication (GunnMoore & Cameron, 2004;Mills, Redgate, & Landsberg, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1e3 Although most cat owners believe their cats get on well with people, human directed aggression is a common problem. 4e6 Scientific reports suggest that aggression towards either people or among cats accounts for between 12 and 47% of the total behavioural problems reported by owners, 7e11 although the concept of aggression in cats is often not well defined, for example, some authors (eg, Overall 12 ) consider urine spraying to be a passive form of aggression and the finding that the response to certain treatments for urine spraying is affected by overt physical aggression, 13 may support this idea. However, in common parlance aggression is often taken to include elements of threat and acts resulting in harm.…”
mentioning
confidence: 99%